First report on Cretaceous vertebrates from the Algerian Kem Kem beds. A new procoelous salamander from the Cenomanian, with remarks on African Caudata - (:unkn) unknown (My University, 2018)
In northwestern Africa, the Kem Kem plateau is a major source of continental Cenomanian fossils. The plateau extends across the Algerian–Moroccan border but, unlike the intensely worked Moroccan part, the Algerian side of the Kem Kem beds has received less attention. However, recent field work in Algeria resulted in the recovery of a locality that yielded a promising vertebrate assemblage. Among the fossils is a trunk vertebra belonging to a salamander, a group whose remains are extremely rare in Africa. The vertebra is procoelous and it presents combination of characters that suggest it belongs to a new taxon of unknown affinities. Although the putative new taxon is represented by a single specimen that is too poorly preserved to be formally named, the discovery is important for showing that salamanders were more diversified than expected in the Cretaceous of Africa.
Keywords: African Research